NG2 Glia Generate New Oligodendrocytes But Few Astrocytes in a Murine Experimental Autoimmune Encephalomyelitis Model of Demyelinating Disease - Tripathi, Richa B. (Society for Neuroscience, 2010)
The adult mammalian brain and spinal cord contain glial precursors that express platelet-derived growth factor receptor α subunit (PDGFRA) and the NG2 proteoglycan. These “NG2 cells” descend from oligodendrocyte precursors in the perinatal CNS and continue to generate myelinating oligodendrocytes in the gray and white matter of the postnatal brain. It has been proposed that NG2 cells can also generate reactive astrocytes at sites of CNS injury or demyelination. To test this we examined the fates of PDGFRA/NG2 cells in the mouse spinal cord during experimental autoimmune encephalomyelitis (EAE)—a demyelinating condition that models some aspects of multiple sclerosis in humans. We administered tamoxifen to Pdgfra-CreER(T2):Rosa26R-YFP mice to induce yellow fluorescent protein (YFP) expression in PDGFRA/NG2 cells and their differentiated progeny. We subsequently induced EAE and observed a large (>4-fold) increase in the local density of YFP(+) cells, >90% of which were oligodendrocyte lineage cells. Many of these became CC1-positive, NG2-negative differentiated oligodendrocytes that expressed myelin markers CNP and Tmem10/Opalin. PDGFRA/NG2 cells generated very few GFAP(+)-reactive astrocytes (1–2% of all YFP(+) cells) or NeuN(+) neurons (<0.02%). Thus, PDGFRA/NG2 cells act predominantly as a reservoir of new oligodendrocytes in the demyelinated spinal cord.